Assessment of health‐related quality of life and health utilities in Australian patients with cirrhosis. Issue 1 (10th December 2020) - McPhail, Steven M; Amarasena, Samath; Stuart, Katherine A; Hayward, Kelly; Gupta, Rohit; Brain, David; Hartel, Gunter; Rahman, Tony; Clark, Paul J; Bernardes, Christina M; Skoien, Richard; Mckillen, Benjamin; et al.
Abstract: Background and Aim: Health‐related quality‐of‐life measurements are important to understand lived experiences of patients who have cirrhosis. These measures also inform economic evaluations by modelling quality‐adjusted life years (QALYs). We aimed to describe health‐related quality of life, specifically multiattribute utility (scale anchors of death = 0.00 and full health = 1.00), across various stages and etiologies of cirrhosis. Methods: Face‐to‐face interviews were used to collect Short Form 36 (SF‐36) questionnaire responses from CirCare study participants with cirrhosis (June 2017 to December 2018). The severity of cirrhosis was assessed using the Child‐Pugh score classified as class A (5–6 points), B (7–9), or C (10–15) and by the absence ("compensated") versus presence ("decompensated") of cirrhosis‐related complications. Results: Patients ( n = 562, average 59.8 years [SD = 11.0], male 69.9%) had a range of primary etiologies (alcohol‐related 35.2%, chronic hepatitis C 25.4%, non‐alcoholic fatty liver disease (NAFLD) 25.1%, chronic hepatitis B 5.9%, "other" 8.4%). Significantly lower (all P < 0.001) mean multiattribute utility was observed in the health states of patients with decompensated (mean = 0.62, SD = 0.15) versus compensated cirrhosis (mean = 0.68, SD = 0.12), Child‐Pugh class C (mean = 0.59, SD = 0.15) or B (mean = 0.63, SD = 0.15) versus A (mean = 0.68, SD = 0.16), and between those of working age (18–64 years; mean = 0.64, SD = 0.16) versus those aged 65+ years (mean = 0.70, SD = 0.16). The greatest decrements in health‐related quality of life relative to Australian population norms were observed across physical SF‐36 domains. Conclusions: Persons with more advanced cirrhosis report greater life impacts. Estimates from this study are suitable for informing economic evaluations, particularly cost‐utility modelling, which captures the benefits of effective prevention, surveillance, and treatments on both the quality and quantity of patients' lives. Abstract : Measuring health‐related quality of life is important for understanding patients' experiences living with cirrhosis. Multiattribute utility is a summary measure commonly derived from health‐related quality‐of‐life questionnaires by applying population‐based preference weights with anchors of death (0.00) and perfect health (1.00) and is used in health state modelling, including economic evaluations that incorporate quality‐adjusted life years (known as QALYs). Here, we report health‐related quality‐of‐life and multiattribute utility values for a range of cirrhosis disease stages. These values will inform both clinical and economic research, including cost‐effectiveness modelling that captures benefits to both the quantity and quality of people's lives through the better prevention and management of cirrhosis.